Evaluation of Apoptosis and Cytotoxicity Induction Using a Recombinant Newcastle Disease Virus Expressing Human IFN-γ in Human Prostate Cancer Cells In Vitro - Aldo Rojas-Neyra; Katherine Calderón; Brigith Carbajal-Lévano; Gloria Guerrero-Fonseca; Gisela Isasi-Rivas; Ana Chumbe; Ray W. Izquierdo-Lara; Astrid Poma-Acevedo; Freddy Ygnacio; Dora Rios-Matos; Manolo Fernández-Sánchez; Manolo Fernández-Díaz (Biomedicines, 2025)
Background/Objectives: Prostate cancer is the second most common type of cancer diagnosed in men. Various treatments for this cancer, such as radiation therapy, surgery, and systemic therapy, can cause side effects in patients; therefore, there is a need to develop new treatment alternatives. One promising approach is virotherapy, which involves using oncolytic viruses (OVs), such as the recombinant Newcastle disease virus (rNDV). Methods: We used the lentogenic rNDV rLS1 strain (the control virus) as our backbone to develop two highly fusogenic rNDVs: rFLCF5nt (the parental virus) and rFLCF5nt-IFN-γ (rFLCF5nt expressing human interferon-gamma (IFN-γ)). We evaluated their oncolytic properties in a prostate cancer cell line (DU145). Results: The results showed the expression and stability of the IFN-γ protein, as confirmed using Western blotting after ten passages in specific pathogen-free chicken embryo eggs using the IFN-γ-expressing virus. Additionally, we detected a significantly high oncolytic activity in DU145 cells infected with the parental virus or the IFN-γ-expressing virus using MTS (a cell viability assay) and Annexin V-PE assays compared with the control virus (p < 0.0001 for both). Conclusions: In conclusion, our data show that IFN-γ-expressing virus can decrease cell viability and induce apoptosis in human prostate cancer in vitro.